Manufacturing of pasta from the sustitution of wheat using subutilized raw materials - Granito, Marisela; Torres, Alexia; Guerra, Marisa (Rev. Téc. Fac. Ing. Univ. Zulia)
ln Venezuela the maize and mayonnaise industries produces as surplus the deffated corn germ (GDM) high in protein and dietary fiber and the dehydrated egg white (CHD). Pumpkin (Cucurbita maxima) (AF), an important source of provitamin An underutilized by the food industry. Considering that pasta is made primarely with semola (S) totally imported, we evaluated the factibilitty of parliatly substituting (S). Formulations were prepared using sustitutions levels of 5, 10, 15 and 25% of (GDM), 15% of (AF) and 0.3 to 3.0% of (CHD).The protein levels, dietary fiber and minerals were modified from 8 to 100% in reference to comercial pasta. Cooking test indicates that the minimun cooking time and losses showed no difference with the control, the PER and NPR values increased 3,58 times and 78% respectively. No estadistical diference was found between pasta with menor level of sustitution and the control. The former had better aceptance. We conclude that substituting S for GDM (5-25%), CHD (0.3-3.0%) and AF (15%) in the formulation of pasta is feasible. Besides this represents a reduction of 22% in production costs.